A brief note on Harnack-type estimates for singular parabolic nonlinear operators - Eurica Henriques; Simone Ciani (Bruno Pini Mathematical Analysis Seminar, 2024)
In this brief note we introduce Harnack-type inequalities, which are typical in the context of singular nonlinear parabolic operators, and describe their state of art in the context of anisotropic operators.